Time to death and its predictors among neonates admitted with sepsis in neonatal intensive care unit at comprehensive specialized hospitals in Northeast Ethiopia - Wudu, Muluken Amare; Bekalu, Yemane Eshetu; Wondifraw, Endalk Birrie; Birhanu, Tarikua Afework; Hailu, Molla Kassa; Belete, Melaku Ashagire; Endeshaw, Yaregal Semanew (Frontiers in Pediatrics, 2024)
In impoverished nations like Ethiopia, neonatal sepsis contributes significantly to neonatal mortality. Despite variations in the specific timing of death and predictors of neonatal mortality associated with sepsis across different settings, there's limited documented information in the Neonatal Intensive Care Units of northeastern Ethiopia. Consequently, the aim of this study was to determine time to death and its predictors among neonates with sepsis admitted to Neonatal Intensive Care Units in comprehensive specialized hospitals in northeastern Ethiopia Methods: A prospective cohort study conducted at the institution level involved 306 neonates diagnosed with sepsis. Data collection utilized face-to-face interviews and chart reviews.Subsequently, the data were inputted into Epi-data version 4.6 and later analyzed using STATA version 17. The median time to death was determined, and both the Kaplan-Meier curve and logrank test were applied. Furthermore, a Cox proportional hazard regression model was utilized to identify predictors of neonatal mortality associated with sepsis.The cumulative incidence of mortality among neonates admitted with sepsis was 34% (95% CI: 28.9-39.5%). The neonatal mortality rate stood at 51 (95% CI: 42.1, 62) per 1,000 neonates admitted to the intensive care units with sepsis over a total of 1854 person-days of observation. Additionally, the median time to death was 13 days (IQR = 5-23 days).Tachypnea [AHR 6.2 (95% CI: 1.5-9.7)], respiratory distress syndrome [AHR 2.1 (95% CI: 1.3-3.5)], lethargy [AHR 1.8 (95% CI: 1.2-2.6)], preterm birth [AHR 1.8 (95% CI: 1.2-2.7)], continuous positive airway pressure use [AHR 2.1 (95% CI: 1.3-3.4)], home delivery [AHR 2.63 (95% CI:1.1-6.4)], Subgalea hemorrhage [AHR 1.8 (95% CI: 1.1-3.9)], and low platelet count [AHR 5.9 (95% CI: 2.3-8.6)] were found to be predictors of time to death in neonates with sepsis.The study revealed an alarmingly high neonatal mortality rate among septic neonates, underscoring the urgency for intervention. Enhancing the quality of care in neonatal intensive care units, bolstering infection prevention during procedures such as continuous positive airway pressure, exercising caution with locally made accessories, and reinforcing a culture of institutional delivery are critical in curbing neonatal sepsis-related mortalities.